Assessment of cardiac radiation dose in the Co-60 prone-based stereotactic partial breast irradiation using distance metrics - Kwon, Young Suk; Parsons, David; Arbab, Mona; Wandrey, Narine; Yarlagadda, Prashant; Stojadinovic, Strahinja; Lu, Weiguo; Alluri, Prasanna; Li, Xingzhe; Chiu, Tsuicheng; Lin, Muhan; Chen, Liyuan; et al. (Frontiers in Oncology, 2025)
Purpose/objective(s)The GammaPod™ (GP) system, a contemporary platform dedicated to breast cancer (BC) radiotherapy, facilitates the delivery of accelerated partial breast irradiation (APBI) via the Co-60 prone-based stereotactic partial breast irradiation (CP-sPBI) technique. The precise CP-sPBI configuration permits reduced planning target volume (PTV) margins compared to other APBI techniques, creating an increased separation between PTV and organs at risk (OARs). This study explores the variability of heart-to-PTV distance and its effects on cardiac dosimetry.Materials/methodsAn APBI database of 102 consecutive patients treated with CP-sPBI between March 2019 and February 2023 was queried for retrospective analysis. Statistical analyses were performed to evaluate the mean and maximum (max) heart and left anterior descending artery (LAD) doses based on two parameters: 1) D-H, the minimum distance between the heart and the lumpectomy cavity PTV, and 2) D-LAD, the minimum distance between the LAD and the lumpectomy cavity PTV. The median values of D-H and D-LAD, measured on either axial or sagittal planes, were employed to categorize patients based on cardiac dose levels.ResultsThe analysis revealed a statistically significant difference in the mean and max heart dose between patients with left-sided and right-sided breast cancer. Specifically, in left-sided breast cancer patients, median D-H and D-LAD cutoffs were identified as 2.67 and 3.22 cm, respectively. Patients with D-H less than 2.67 cm exhibited significantly higher mean (1.77 vs. 0.75 Gy; p < 0.01) and max heart doses (15.21 vs. 4.38 Gy; p < 0.01) compared to those with D-H greater than or equal to 2.67 cm. Similarly, lower D-LAD values (<3.22 cm) demonstrated a statistically significant association with increased arterial dose compared to higher D-LAD values (≥3.22 cm).ConclusionsLeveraging its sharp dose fall-off characteristic, the GP treatment delivery system facilitates the delivery of five-fraction APBI while maintaining acceptable cardiac dosimetry parameters. This is particularly advantageous for tumors situated further from the heart because heart doses dissipate with distance. The estimates of heart dose based on the distance to the heart and LAD from PTV have the potential to serve as a valuable tool for clinicians, aiding in more refined risk evaluation and patient selection for CP-sPBI.